Development And Actualization of Students' Social Intelligence in The Islamic Religious Education Learning - Uswatun Hasanah; Ida Faridatul Hasanah; Agnila Farasi (Cendekia, 2024)
The current post-pandemic period has a significant impact on learning, particularly in Islamic religious education subjects. As a result, many students are less focused on attending lessons, their learning motivation and participation levels are decreasing, and their social intelligence is low because they are used to online learning, which has few face-to-face meetings. They are unable to adapt to the transition from previously online to hybrid learning methods. This study aimed to discover the Islamic religious education teachers' strategies for fostering and actualizing students' social intelligence in the post-pandemic period at MA AL-Hikmah Bandar Lampung. The research method employed was qualitative field research. The data collection techniques employed were interviews, observation, and documentation. The data analysis techniques employed were data reduction, data presentation, and conclusion. Triangulation can be used to validate the data. The research findings revealed that in order to develop and actualize students' social intelligence, teachers employed cooperative and affective learning strategies that are implemented in four areas: methods, media, learning materials, and learning evaluation. Finally, fostering and actualizing students' social intelligence necessitates creative and innovative strategies to ensure proper development.